Ancient Gaelic Inscriptions in Scotland (Proceedings of the Society of Antiquaries of Scotland, 1852)
W.F. Skene read a communication on ancient inscribed Scottish monuments with particular reference to the Ogham inscriptions on the monuments at Newton and Golspie. He then went on to say that such inscriptions, especially when legible were highly valuable in ascertaining the origin, period, and character of the sculptured stones of Scotland. By analysis of two inscriptions from Iona, Skene elucidates a four-line inscription on the stone at St. Vigeans.